(untitled) (Fiep Bulletin - online, 2012)
Objective. This study aimed to investigate the incidence of episiotomy conducted in deliveries in a university hospital and its relation to maternal variables. Methods. This is a retrospective cross-sectional study conducted in a Teaching Hospital at Northwest Paraná. The study was conducted from January 2007 to June 2009, in which a total of 681 normal deliveries were analyzed. Results. The mean age was 23.97 years; episiotomy was performed in 276 (40.73%) of them, with middle-side episiotomy the most frequent (94.20%). No laceration occurred in 89.49% of the patients undergoing episiotomy. Most women who underwent the procedure were adults (56.89%). Episiotomy was more prevalent among primigravidae (67.75%). The primiparous were 16 times more likely to receive assistance than the multiparous. Conclusion. The prevalence of episiotomy in the hospital was high, as well as other interventions, such as the use of oxytocin for acceleration of labor. Comprehensive studies that assist in determining the need for episiotomy, type, advantages, and risks in the delivery process for both mother and infant should be carried out to achieve excellence in monitoring pregnant women.